Valorization of water treatment sludge from a circular economy perspective: the case of the WTP of Areias de Vilar - Mattoso, A. P. (2023)
The water treatment process generates waste called Water Treatment "sludge" (WTS), which has added value and is therefore viable for use in other production processes, thus applying the principle of circular economy. This paper aims to present the results of the diagnosis of the Water Treatment Plant (WTP) of Areias de Vilar, Portugal. The WTP treats raw surface water (abstracted from river Cávado) by treatment scheme composed of the following unit processes: pre-oxidation, remineralization, coagulation/flocculation, decantation, fast filtration, disinfection and pH correction. In 2022, this plant produced more than 29 million m3 of treated water and generated about 928 ton of sludge. After drying, a significant part of these sludges consists of silica (SiO2), alumina (Al2O3) and hematite (Fe2O3), in addition to organic matter, aluminium hydroxide (Al(OH)3), other oxidized metals, including calcium oxide (CaO) (mainly originated in the remineralization step), activated carbon and polyelectrolyte. The Areias de Vilar WTP has implemented a more efficient drying process (natural oven), to obtain a dry solid waste with more suitable characteristics for its recovery as a raw material in the construction industry, promoting a more sustainable approach from the perspective of the circular economy.